A new Sesleria juncifolia association from south-eastern Italy and its position in the amphi-Adriatic biogeographical context - Di Pietro, Romeo; Wagensommer, Robert Philipp (Acta Botanica Croatica, 2014)
The Sesleria juncifolia calcareous grasslands in the Apulia region (southern Italy) were studied on the basis of 24 phytosociological relevés. According to UPGMA cluster analysis division and NMDS ordination the relevés were classified into four major groups which gave rise to three sub-associations (Gargano) and a geographically impoverished variant (Alta Murgia). The new association Stipo austroitalicae-Seslerietum juncifoliae ass. nova was proposed. Due to the relict and scattered distribution of Sesleria juncifolia in Apulia region, the variances in species composition amongst the different subassociations are mainly influenced by local factors. The community Stipo-Seslerietum should be included in the south-eastern Italian alliance Hippocrepido-Stipion austroitalicae while at the rank of order it exhibits intermediate coenological features between the Central - South Apennine endemic suborder Festuco-Seslerienalia nitidae and the North-West Balkan order Scorzonero-Chrysopogonetalia.